Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5812/aapm.87415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sedation Quality of Etomidate, Propofol, and Midazolam in Combination with Fentanyl During Phacoemulsification Cataract Surgery: A Double-Blind, Randomized, Controlled, Clinical Trial

Abstract: Background According to the favorable effects of combination therapy to provide better sedation during phacoemulsification and lack of any studies investigating the sedative effect of etomidate, propofol, and midazolam in combination with fentanyl during the procedure. Objectives The current study aimed at comparing the sedative properties of the mentioned three combination therapies in this field. Methods The current double-blind, randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…In the current study, we recorded the level of sedation based on the Ramsay sedation scale, which is useful in assessing the clinical effects of sedative agents (11,12). Our results are compatible with the literature where those administered with pregabalin premedication experienced less pain during the procedure, as well as higher sedation scores and low anxiety levels, especially in other ophthalmic surgeries (13,14).…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, we recorded the level of sedation based on the Ramsay sedation scale, which is useful in assessing the clinical effects of sedative agents (11,12). Our results are compatible with the literature where those administered with pregabalin premedication experienced less pain during the procedure, as well as higher sedation scores and low anxiety levels, especially in other ophthalmic surgeries (13,14).…”
Section: Discussionsupporting
confidence: 86%
“…The primary aim of this study was to investigate the effect of Benson's non-pharmacological relaxation therapy on preoperative anxiety and the amounts of propofol consumption for the induction and maintenance of anesthesia during cataract surgery. One of the most surgeries in ophthalmology is cataract surgery (10,11). Based on the obtained results, it can be concluded that Benson's relaxation method effectively reduced preparative anxiety in patients of this study who underwent cataract surgery.…”
Section: Discussionmentioning
confidence: 54%
“…Midazolam and propofol are the commonly used agents, while a short acting opioid (e.g., alfentanil and fentanyl) is sometimes added to supplement analgesia ( 46 ). The Ramsay sedation score may be useful to assess their clinical effects ( 47 ).…”
Section: Sedation With Local/regional Anesthesiamentioning
confidence: 99%